MONITORING APPLICATIONS DIVISION PROMOTION ACTIVITIES IN PT PT AMERTA INDAH OTSUKA USING VISUAL BASIC 6.0 - Niky Lauda; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2007)
The Importance of Controlling in every activity within an enterprise is one of the keysuccess of the company to achieve the goal. Writing provides a data processinginformation system design activities conducted by the Promotion Division of PTAmerta Indah Otsuka using Visual Basic 6.0. With the expected applications ofexisting data on all promotional activities can be obtained quickly, accurately. So thatcan assist in making the Sales Strategy.